Seismic swarms in the Pollino seismic gap: Positive fault inversion within a popup structure - De Gori, Pasquale; Lucente, Francesco Pio; Govoni, Aladino; Margheriti, Lucia; Chiarabba, Claudio (Frontiers in Earth Science, 2022)
Seismic swarms frequently occur along continental fault systems and their relation with large earthquakes is often contradictory. Such a case is documented in the Pollino mountain range of southern Italy, a decoupling zone where the belt-normal stretching drastically rotates accommodating the differential SE-retreat of the Ionian slab. The paucity of historical large earthquakes has led to hypothesize the presence of a seismic gap. A long-lasting seismic swarm that climaxed with a ML=5.2 earthquake in October 2012 was therefore thought as a possible signal of an impending large earthquake filling the gap. Seismicity data collected during a four-years long monitoring are a powerful microscope to look through the seismic swarm. In this study, we present accurate relocations for 2385 earthquakes and high-resolution Vp and Vp/Vs models of the fault system. Seismicity occurred on two separate normal faults that were formerly part of a thrusts and back-thrusts system, originally formed as a pop-up at restraining bends of the Pollino fault, a wrench fault system that inverted the original left lateral sense of slip accommodating a differential motion induced by the southward retreat of the Ionian slab.